Motor performance and behavior of immature rats are not compromised by a high dose of topiramate - Alaverdashvili, M; Mareš, Pavel; Kubová, Hana (Epilepsy & behavior, 2005)
The first step in a study of possible cognitive side effects of topiramate in immature rats is to determine if and how topiramate (TPM) influences motor ability and spontaneous behavior. We therefore studied the effects of TPM on motor performance of 12- and 25-day-old rats using age-appropriate tests. Spontaneous behavior in the open field was studied in 25-day-old animals only. TPM was administered intraperitoneally at 80 and/or 160 mg/kg; control rats were injected with solvent (dimethylsulfoxide). A battery of motor tests was conducted before and 1, 3, and 24 hours after administration; behavior in the open field was recorded 2 and 24 hours after TPM administration. The effects of TPM on motor performance were similar to those of solvent. A few differences were found only at the 3-hour interval in 12-day-old rats. Behavior in the open field was not impaired by TPM; on the contrary, an apparent anxiolytic effect was observed. Habituation (a decrease in locomotor activity during the 5-minute observation period), a form of simple nonassociative learning, was also not compromised by TPM. A single high dose of TPM resulted only in transient changes in motor performance. A possible anxiolytic effect observed in 25-day-old rats should be studied.
Keywords: Anticonvulsants; pátrací chování; pohybová aktivita; chování zvířat; metoda rotující tyčky; antikonvulziva; Dose-Response Relationship, Drug; Rotarod Performance Test; novorozená zvířata; financování organizované; věkové faktory; krysa rodu Rattus; Financing, Organized; fruktosa; zvířata; Exploratory Behavior; potkani Wistar; Animals, Newborn; Rats, Wistar; Psychomotor Performance; Rats; vztah mezi dávkou a účinkem léčiva; Body Weight; Age Factors; Motor Activity; Animals; tělesná hmotnost; Fructose; Behavior, Animal; psychomotorický výkon